PURCHASING POWER AND REPLACEMENT COST CONCEPTS–ARE THEY RELATED? - Henderiksen, Eldon S. (The Accounting Review, 1963)
Abstract Considerable progress has been made recently in clarifying the different effects on the business firm and on financial accounting of changes in general prices on the one hand and of changes in specific prices on the other. Changes in prices in general are assumed to reflect changes in the general value of the dollar and in general purchasing power. Changes in specific prices are assumed to reflect changes in the structure of prices in the economy without changing the general level of prices. The importance of this distinction between general and special price changes stems from the relevancy of at least two concepts of net income, enterprise net income computed on the basis of a common dollar and net operating income excluding gains and losses arising from the holding of assets while theft specific prices change. The latter concept requires adjustments of both general and specific price changes when movements are occurring in the level of prices as well as in the structure of prices, the effect of specific price changes cannot be measured unless the accounts are first adjusted for changes in the general price level.